Outcomes of transcatheter mitral valve repair from the latest nationwide inpatient sample database 2016–2017. (25th November 2020) - Mehta, H; Kurpad, K; Okoh, A; Singh, S; Berman, J; Hawthorne, K
Abstract: Background: Transcatheter mitral valve repair (TMVR) is an alternative treatment option for severe mitral regurgitation (severe MR) in patients with high surgical risk. Previous studies have demonstrated safety and efficacy of TMVR. The aim of our study was to assess comorbid and patient outcome data in a nationwide sample. Methods: From the Nationwide Inpatient Sample (NIS) 2016–2017, all adult patients with mitral valve regurgitation were identified. Patients were divided into two group- TMVR and SMVR (surgical mitral valve repair). Patients requiring surgical valve replacement were excluded. Primary outcomes were inpatient mortality and length of stay. Multivariate analysis was performed to adjust for comorbidities. Results: A total of 6211 TMVR were performed, while 3789 SMVR were performed. TMVR patients were older (78.34 vs 62.26 years) and had more females (48.86 vs 36.18%). Comorbidities were higher in the TMVR group [heart failure (81.02 vs 46.02%, p<0.001), diabetes mellitus (27.13 vs 15.81%, p<0.001), chronic kidney disease (39.3 vs 13.7%, p<0.001), chronic lung disease (27.13 vs 16.65%, p<0.001). Complications were higher in the SMVR [Cardiogenic shock (3.8 vs 6%, p=0.007), blood transfusion requirement (19.44 vs 4.85%, p=0.001), respiratory failure (10.99 vs 7.37, p=0.012)]. Mean length of stay was higher with SMVR [8.60±0.22 (4.139–5.17) days] compared to TMVR [4.65±0.26 (8.167–9.03) days]. In-patient mortality was lower in TMVR (2.01 vs 2.45%, p-0.02). After adjusting for comorbidities on multivariate analysis, there was no difference in mortality between the groups (adjusted OR=1.081±0.419 (0.506–2.311). Conclusion: From nationwide data, we report TMVR as a relatively safe treatment modality for severe MR, with comparable inpatient mortality and fewer complications than SMVR, despite having a significantly higher burden of comorbidities. Funding Acknowledgement: Type of funding source: None